67.9k views
3 votes
16.2=2.7(h+1) solve for h

2 Answers

6 votes

Explanation:

16.2 = 2.7(h+1)

2.7(h+1) = 16.2

(h+1) = 16.2 ÷ 2.7

h+1 = 6

h = 5

User Mahbub
by
5.2k points
4 votes

Answer:


\boxed{ \bold{ \huge{ \boxed{ \sf{h = 5}}}}}

Explanation:


\bigstar{ \sf{ \: \: 16. 2 = 2.7( \: h \: + \: 1)}}


\tt{Step \: 1 \: } : Swap the sides of the equation


\longmapsto{ \sf{2.7(h + 1) = 16.2}}


\tt{Step \: 2 \: } : Distribute 2.7 through the parentheses


\longmapsto{ \sf{2.7 * h + 2.7 * 1 = 16.2}}


\longmapsto{ \sf{2.7h + 2.7 = 16.2}}


\tt{Step \: 3 \: } : Move 2.7 to right hand side and change it's sign


\longmapsto{ \sf{2.7h = 16.2 - 2.7}}


\tt{Step \: 4 \: } : Subtract 2.7 from 16.2


\longmapsto{ \sf{2.7h = 13.5}}


\tt{Step \: 5 \: } : Divide both sides by 2.7


\longmapsto{ \sf{ (2.7h)/(2.7) = (13.5)/(2.7)}}


\tt{Step \: 6 \: } : Calculate


\longmapsto{ \sf{h = 5}}

The value of h is 5

Hope I helped!

Best regards! :D

~TheAnimeGirl

User AmmoPT
by
4.3k points